Controlling azimuthal spoke modes in a cylindrical Hall thruster using a segmented anode. (25th October 2018) - Shi, Yuan; Raitses, Yevgeny; Diallo, Ahmed
Abstract: Azimuthal spoke-like modes commonly occur inE  × B discharges. The natural occurrence of the spoke mode is correlated with changes of plasma parameters. Here, instead of allowing these changes to occur naturally, we report a technique for actively controlling the spoke by adjusting the boundary condition at the anode. The technique is demonstrated using a cylindrical Hall thruster equipped with a segmented anode. By varying the voltage and the relative phases of the anode segments, properties of the azimuthal mode can be altered substantially, as shown by fast camera images and probe diagnostics. This technique may be extended to other Hall discharges in order to either induce or suppress azimuthal activities, and thereby controlling the operation and the performance of the devices.